Optimal fertilizer rate and sowing density can improve oat quality, yield and N and P comprehensive efficiency in the Loess Plateau of China - Zhang, Ruochen; Wang, Yue; Malik, Kamran; Wang, Jianjun; Zhao, Guiqin; Li, Chunjie (Frontiers in Plant Science, 2025)
IntroductionOat is a nutritious native species in Loess Plateau for forage and animal husbandry. By focusing on the sowing density and fertilizer rate, oats can achieve better productivity performance while maximizing nutrients use efficiency. However, the information on the responses of oats yield, quality and nutrients use efficiency to fertilization and sowing density is limited.MethodsIn this study, from 2022 to 2023, a two-factor randomized block design field trial was conducted in Loess Plateau. The three sowing densities (SD, L: 75 kg/ha; M: 150 kg/ha; H: 225 kg/ha) were coupled with six fertilizer rates (FR, N0P0: no fertilization; N2: 100 N kg/ha; P2: 90 P kg/ha; N1P2: 50 N kg/ha, 90 P kg/ha; N2P1: 100 N kg/ha, 45 P kg/ha; N2P2: 100 N kg/ha, 90 P kg/ha). The effects of FR and SD on oat forage yield, quality, agronomic efficiency (AE), N/P content, uptake and its uptake efficiency and recover efficiency were investigated. In order to compare N/P efficiency more intuitively, we combined N/P content, N/P uptake, N/P uptake efficiency and N/P recover efficiency to calculate N/P comprehensive efficiency.ResultsOverall, the M-N1P2 treatment promoted the oat growth and achieved the maximum oat forage yield and quality. In the M treatment, the average crude protein (CP) content, relative feed value (RFV), forage yield, CP yield, N content, P content, N uptake and P uptake increased by 20.2%, 4.9%, 73.2%, 100%, 30.4%, 26.3%, 128.5% and 118.4%, respectively, compared with those under the no fertilization treatment; while the average neutral detergent fiber (NDF) decreased by 2.6% in the N1P2 treatment compared to no fertilization treatment. The optimum agronomic efficiency (AE), N uptake efficiency and N recover efficiency were also observed under M-N1P2 during both years. The comprehensive analysis revealed M-N1P2 also had the highest N comprehensive efficiency and P comprehensive efficiency among all treatments. The results of correlation analysis revealed significant positive correlations (P< 0.05) of forage yield and CP with nutrients efficiency of oat, but negative correlations with fiber content.DiscussionThis study determined the appropriate sowing density and fertilization rate (M-N1P2) for cultivating oat in Loess Plateau and provided a foundation for promoting productivity of oats.